Implementasi Nilai-Nilai Peace Education pada Santri Gen-Z di Pesantren Mahasiswa An Najah Purwokerto - Ulul Huda; Fauzi Fauzi (Matan : Journal of Islam and Muslim Society, 2026)
Abstract: Gen Z who was born between 1997-2012 is a generation that was born full of ambition, brave, quite critical human beings, and high curiosity. But they also have a weak point, namely a generation that gets bored easily, sees results more than processes, is used to instant things, easily stressed, easily affected by small things and others. With this weak point, it is feared that Gen Z will be easily provoked by hoax information, fall into misleading ideas, so that violence, destruction, and war can easily be created. Therefore, pesantren are present as a shield and a forum for Gen Z to learn about religion, humanization, tolerance, multiculturalism and inclusiveness. From these indicators, peace education values will be created. Descriptive qualitative research methods of phenomenological study type. Data collection techniques by: 1) Interviews 2) Field observations 3) Documentation studies. The analysis technique of this research by: 1) data reduction, 2) data presentation, and 3) verification, then continued by checking the wetness of the data by means of triangulation. The result of this study is that strengthening peace education values in Gen Z students in pesantren can be done by a) Implementing Inclusive Peace Education Values. b) Implementation of Multicultural-based Peace Education Values. c) Implementation of Peace Education Values based on Humanism. d) Implementation of Peace Education Values based on Tolerance. Keyword: Gen Z Students, Islamic Boarding School, Peace Education Abstrak: Gen Z yang lahir antara tahun 1997-2012 yang lalu merupakan generasi yang terlahir penuh ambisi, pemberani, manusia cukup kritis, mempunyai rasa ingin tahu yang tinggi. Namun juga mereka memiliki titik kelemahan yaitu generasi yang mudah bosan, lebih melihat hasil dari pada proses, terbiasa dengan hal-hal instan, mudah stress, mudah terpengaruh oleh hal-hal kecil dan lainnya. Dengan adanya titik kelemahan tersebut dikhawatirkan Gen Z akan mudah terprofokasi oleh informasi hoax, terjerumus paham-paham yang menyesatkan, sehingga mudah terciptanya kekerasan, kehancuran, dan peperangan. Oleh karena itu pesantren hadir sebagai tameng dan wadah bagi Gen Z untuk belajar tentang agama, humanisasi, toleransi, multikultural dan inklusif. Dari indikator tersebut maka akan tercipta nilai-nilai peace education (Pendidikan damai). Metode penelitian kualitatif deskriptif jenis studi fenomenologis. Teknik pengumpulan data dengan cara: 1)Wawancara 2) Observasi lapangan 3) studi dokumentasi. Teknik analisis penelitian ini dengan: 1) reduksi data 2) penyajian data, serta 3) verifikasi, kemudian dilanjutkan dengan pengecekan kebasahan data dengan cara triangulasi. Hasil penelitian ini adalah bahwa penguatan nilai-nilai peace education pada santri Gen Z dipesantren dapat dilakukan dengan a) Implemetasi Nilai-Nilai Peace Education berbasis Inklusif. b) Implemetasi Nilai-Nilai Peace Education berbasis Multikultural. c) Implemetasi Nilai-Nilai Peace Education berbasis Humanisme. d) Implemetasi Nilai-Nilai Peace Education berbasis Toleransi. Kata kunci: Santri Gen Z, Pesantren, Peace Education